(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2019)
As world demand for soybeans increases, it is necessary to use alternative techniques to increase the production of the crop in a sustainable way. Biological nitrogen fixation - BNF performed by diazotrophic bacteria is considered an efficient and economical source for N supply to the crop. This study aimed to evaluate soybean productivity and soil bioindicators as a function of the inoculation of Bradyrhizobium japonicum isolated and the co-inoculation with Azospirillum brasilense in succession of autumn-winter crops. The experiment was carried out in the experimental area of Embrapa Western Agriculture, in Dourados, MS, in the 2016/2017 harvest season. The experimental design was in randomized blocks in subdivided plots with three replicates. In the plots were allocated the four autumn-winter crops (single corn, corn intercropped with Brachiaria ruziziensis, cowpea and B. ruziziensis), and in the subplots inoculation via seeds: without inoculation (control); inoculation with B. japonicum and co-inoculation of B. japonicum + A. brasilense. No significant effect of inoculation methods was observed on the studied variables. The autumn-winter crops influence the grain yield, which the soybeans cultivated in succession to intercropping maize and cowpea achieved better averages. The microbial biomass carbon, metabolic and microbial quotients were influenced by the crops, being the highest value of microbial biomass carbon found in succession to intercropped corn, in relation to cowpea, B. ruziziensis and single maize. The activity of the acid phosphatase enzyme was not influenced by any factor studied. The use of autumn-winter crops contributes to the performance of soybeans in succession and contribute to the increase of soil microbial biomass. Key words: co-inoculation, soil microbiology, crop rotation, Glycine max L.